(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The world of business has become an important criterion for survival these days. In the context of the realm of business, the liquidity ratio plays an imperative role in all possible ways. It has become the obligatory criteria in analyzing the liquidity ratio for a better understanding of the world of business nuances in general and the status of the company in particular. Analyzing the liquidity ratio guides in taking a bold and smart decision which will, in turn, seek the attention of prospective investors. It is highly essential for small-scale business developers to have a proper analysis of the liquidity ratio for better growth progress. This paper tries to investigate the needs of the liquidity ratio analysis from a business perspective.